2002
DOI: 10.1046/j.1365-2648.2002.02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the outputs of Australian nursing research published 1995–2000

Abstract: Research findings need to be applied in practice to improve patient care. Nurse researchers need to publish their findings and align their research interests to meet national health priorities. They need to be involved in setting these health priorities to ensure that nursing has a place in health research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 13 publications
11
61
0
1
Order By: Relevance
“…An analysis of Australian nursing research output over a five year period identified 509 papers, 101.8 average per year (Borbasi et al, 2002). Whilst these two studies are not directly comparable to this review because of the difference in time span, they do highlight that the number of military nursing research papers over the past 23 years is substantially less.…”
Section: Discussionmentioning
confidence: 82%
“…An analysis of Australian nursing research output over a five year period identified 509 papers, 101.8 average per year (Borbasi et al, 2002). Whilst these two studies are not directly comparable to this review because of the difference in time span, they do highlight that the number of military nursing research papers over the past 23 years is substantially less.…”
Section: Discussionmentioning
confidence: 82%
“…Dates were selected based on prior scoping reviews restricting searches to 5-10 years (Bassalobre Garcia A, 2015; Borbasi et al, 2002; Sun & Larson, 2015) and to narrow the search to only include current research.…”
Section: Review Methodsmentioning
confidence: 99%
“…The variables studied included the general and methodological characteristics of the study based on scoping review recommendations (Armstrong et al, 2011), prior nursing research reviews (Bassalobre Garcia A, 2015; Borbasi et al, 2002; Sun & Larson, 2015), research questions, and by evaluating a subset of included studies (233 full text) to iteratively develop and refine the coding scheme for each category. Consensus of categories and subcategories was met by discussion (Sandelowski, 2010).…”
Section: Review Methodsmentioning
confidence: 99%
“…While there is a need to share knowledge, it is also important to know what is occurring in order to plan future research, arrange for continuing education for nurses, and to plan research conferences. (4) .…”
Section: While Nursing Research Is Flourishing In Latinmentioning
confidence: 99%